KONSEP PENDIDIKAN AKHLAK DALAM ALQURAN UNTUK MEMBANGUN KARAKTER PESERTA DIDIK - Zulkipli Nasution (Jurnal Al-Fatih, 2019)
Education is a fundamental necessity for every human being to success and happiness in the world and the hereafter. Moral education should be the main objective in the education of Islamic morals is part of the spirit of progress of Islamic education. Through a good education berladaskan and bound to the Koran will hopefully produce learners that character based on Moral education in the Holy Quran. The morals of the good in accordance with the guidelines of the Koran will build character of learners. Among one of the Qur'anic method of constructing moral education concept to build the character of learners is a method of story. The methods of the story will make it easier for learners to understand the important messages of Qur'anic verses about moral education in building a character education learners.